High Temperature Co‐Electrolysis as a Key Technology for CO2 Emission Mitigation – A Model‐Based Assessment of CDA and CCU. Issue 8 (22nd June 2020) - Herz, Gregor; Müller, Nils; Adam, Paul; Megel, Stefan; Reichelt, Erik; Jahn, Matthias
Abstract: The mitigation of CO2 emissions is a major challenge for modern society. While the mitigation of energy‐related emissions can be achieved comparatively easy by switching to renewable energy sources, reduction of process‐related industrial emissions is considerably more challenging. To reduce industrial CO2 emissions, two basic routes are available: carbon direct avoidance (CDA) and carbon capture and utilization (CCU). It is shown that in terms of efficiency, CDA is to be favored when applicable. However, for applications where emissions cannot be avoided, CCU can be a viable approach allowing for emission mitigation. Abstract : The application of SOEL technology in CCU and CDA approaches is studied via process modeling. The results of this study highlight the advantages especially of high temperature co‐electrolysis for the purpose of CO2 emission mitigation in industrial applications like steelmaking as well as lime and cement production.